2002
DOI: 10.1128/jvi.76.17.8505-8517.2002
|View full text |Cite
|
Sign up to set email alerts
|

Viral RNA Mutations Are Region Specific and Increased by Ribavirin in a Full-Length Hepatitis C Virus Replication System

Abstract: High rates of genetic variation ensure the survival of RNA viruses. Although this variation is thought to result from error-prone replication, RNA viruses must also maintain highly conserved genomic segments. A balance between conserved and variable viral elements is especially important in order for viruses to avoid "error catastrophe." Ribavirin has been shown to induce error catastrophe in other RNA viruses. We therefore used a novel hepatitis C virus (HCV) replication system to determine relative mutation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
106
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(114 citation statements)
references
References 35 publications
7
106
1
Order By: Relevance
“…In studies using HCV replication models, mutagenic effects of ribavirin have been identified by several 54,[56][57][58][59][60] but not all authors. 61 When infectivity was used as a functional readout for mutagenesis, diminished infectivity was found with ribavirin treatment of HCV cultures.58 , 60 The concentrations of ribavirin needed to achieve mutagenic effects were high (up to 400 uM) and may exceed those achieved in vivo.…”
Section: Ribavirin: Mechanism Of Action Clinical Insightsmentioning
confidence: 99%
“…In studies using HCV replication models, mutagenic effects of ribavirin have been identified by several 54,[56][57][58][59][60] but not all authors. 61 When infectivity was used as a functional readout for mutagenesis, diminished infectivity was found with ribavirin treatment of HCV cultures.58 , 60 The concentrations of ribavirin needed to achieve mutagenic effects were high (up to 400 uM) and may exceed those achieved in vivo.…”
Section: Ribavirin: Mechanism Of Action Clinical Insightsmentioning
confidence: 99%
“…A similar effect of high concentrations of ribavirin has been found in cell cultures infected by RNA viruses belonging to several families, including foot-and-mouth disease virus, Hantaan virus, West Nile virus, and GB virus B, a member of the Flaviviridae family that is closely related to HCV (1,9,16,20,44). In addition, ribavirin has been reported to exert an antiviral effect related to errorprone replication in HCV subgenomic replicons, both in Huh7 cell lines and in a full-length binary HCV replication system (5,20,21,48,53). However, error-prone replication is not the mechanism by which ribavirin acts against arenavirus lymphocytic choriomeningitidis virus or the yellow fever virus, another member of the Flaviviridae family that is related to HCV (24,42).…”
mentioning
confidence: 99%
“…Incorporated ribavirin causes transition mutations (A-to-G, G-to-A) because of its ability to pair with both uracil and cytosine. Ribavirin has been shown to increase error frequency for both poliovirus genomic RNA and hepatitis C replicon synthesis (1)(2)(3). Thus, ribavirin is thought to exert its antiviral activity by increasing the error rate of viral genome replication past the point of ''error catastrophe,'' whereby the fitness of all members of the viral population is reduced.…”
mentioning
confidence: 99%